Industrial processes optimization in digital marketplace context: A case study in ornamental stone sector - Silva, Agostinho (2021)
We are witnessing a transition to a digital economy, popularized by academics and practitioners as the Fourth Industrial Era, also designated as Industry 4.0 (I4.0). Among all the available digital technologies and aiming to optimize the Architecture Engineering and Construction (AEC) supply chain, the Building Information Modelling (BIM) is becoming officially mandatory worldwide. Oriented to a zero-waste, zero-ecological footprint and reduced time to execute the constructions, from the BIM, emerges a new procurement model which will affect many sectors integrating this supply chain, especially those more traditional and fragmented ones, such as the Ornamental Stone sector (OS). Addressing this problem through the Service Science perspective, the objective of this research was to conceptualize an Empirical Framework (EF), to evaluate the impact of the Industry4.0 operations on the Time-to-Deliver the products in a digital marketplace context. By applying this EF to a case study related to the Ornamental Stone in Portugal, it was found a positive impact of Industry 4.0 operations on the delivery time in the digital marketplace context.